AKURASI HASIL PREDIKSI PASANG SURUT PELABUHAN DUMAI MENGGUNAKAN METODE ADMIRALTY - Hendri, Andy; Fauzi, Manyuk; Astari, Kemala Fitri (Jurnal Teknologi dan Rekayasa Sipil, 2024)
The admiralty method is one of common method that used to predict tides. Tidal prediction with admiralty method is done using 15 days and 29 days tidal data. This research aims to compare the accurary of admiralty method’s result. Tidal data of Port C of Pelindo, Dumai has been analyzed using 29 days and 15 days admiralty method. The results of this research indicated that the results of tidal analysis using 29 days admiralty method generated the smallest RMSE (Root Mean Square Error) value of 44.36 cm, however 15 days admiralty method generated the smallest RMSE value of 70.39 m. So, the result of 29 days admiralty method tidal prediction is more accurate than 15 days admiralty method.